If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2(x + -6) = -20 Reorder the terms: 8 + 2(-6 + x) = -20 8 + (-6 * 2 + x * 2) = -20 8 + (-12 + 2x) = -20 Combine like terms: 8 + -12 = -4 -4 + 2x = -20 Solving -4 + 2x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2x = -20 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -20 + 4 2x = -20 + 4 Combine like terms: -20 + 4 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| -4(0)+7y=3 | | x+(x-32)=38 | | 2x-2=2(17)-2 | | r-(24.5-14r)t=2t^2 | | x-1=1/x | | r-(24.5-14r)t=2t | | 2x^2-5x-102=0 | | 2a=0.38 | | -3-2x=0 | | 25y-30=10+20 | | 286=-v+170 | | 10.5r+56t=86t | | 15-u=178 | | -15+-10x=4x | | 56t+10.5r=86t | | -2v+1=0 | | f(4)=2x^3+3x-4 | | 17r-2(3r-1)+3r=r+28 | | 4b=6-3a | | -18-6y=6(1+3y) | | 4(3x-3)-11x(x-2)= | | (5-y)+(6-y)-(-5-y)=0 | | x+(x-11)=57 | | 0=-4t+8 | | 14x-3.5y=43 | | 2.9+(-6.5)= | | 5(3x-3)-14(x-4)= | | 11a-10a+13=-5 | | 2x+7x=19.50 | | -1.5=-4.5 | | 14-2x=-8(x-7) | | -3a= |